2012
DOI: 10.3324/haematol.2012.072991
|View full text |Cite
|
Sign up to set email alerts
|

Donor lymphocyte count and thymic activity predict lymphocyte recovery and outcomes after matched-sibling hematopoietic stem cell transplant

Abstract: Blood Institute institutional review board-approved protocols. Patients and donors provided written informed consent before enrolling in the transplantation protocols. The clinical characteristics of these 220 patients and their respective donors are presented in Table 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Moreover, Treg cell frequency was shown to be reduced by as much as 40% in the peripheral blood of allogeneic HSCT recipients that developed GVHD as compared to autologous or allogeneic HSCT recipients that displayed no signs of GVHD (Magenau et al, 2010). Similar results have also been observed in cGVHD, where the frequency of Treg cells negatively correlated with disease severity (Zorn et al, 2005; Li et al, 2010; McIver et al, 2012). Whereas most human studies have examined peripheral blood Treg cells; Rieger et al assessed mucosal Treg cell frequencies in intestinal biopsies, which are perhaps a more relevant marker of disease.…”
Section: Role Of Treg Cells In Human Gvhdsupporting
confidence: 75%
“…Moreover, Treg cell frequency was shown to be reduced by as much as 40% in the peripheral blood of allogeneic HSCT recipients that developed GVHD as compared to autologous or allogeneic HSCT recipients that displayed no signs of GVHD (Magenau et al, 2010). Similar results have also been observed in cGVHD, where the frequency of Treg cells negatively correlated with disease severity (Zorn et al, 2005; Li et al, 2010; McIver et al, 2012). Whereas most human studies have examined peripheral blood Treg cells; Rieger et al assessed mucosal Treg cell frequencies in intestinal biopsies, which are perhaps a more relevant marker of disease.…”
Section: Role Of Treg Cells In Human Gvhdsupporting
confidence: 75%
“…Magenau et al [11] showed that aGVHD was associated with a decrease of Tregs frequency in the peripheral blood of allo-HSCT recipients; moreover, several reports demonstrated a decreased frequency of Tregs in the peripheral blood of patients with high clinical grades of aGVHD as compared to patients with lower grade aGVHD [12,13]. Similar results have also been observed in cGVHD, where the frequency of Tregs negatively correlated with disease severity [12,14]. However, not all studies have demonstrated a correlation between reduced Tregs frequency and GVHD severity.…”
Section: Role Of Tregs In Human Gvhdsupporting
confidence: 50%
“…To some extent, our results that CD3+ T cells are positively associated with ALC-22 have confirmed the above speculations. McIver et al [38] also have shown that higher T lymphocyte counts in donors are associated with a rapid lymphocyte recovery, a reduced risk of extensive chronic graft-versus-host disease, and superior survival in the recipient following allogeneic HSCT. So, the ALC responding to leukemia during therapy may be CD3+ T cells.…”
Section: Discussionmentioning
confidence: 94%